The complete mitochondrial genome of hawthorn trunk borer, Platypus contaminatus (Coleoptera: Curculionidae: Platypodinae) - Shengchang Lai; Ling Zhang; Peishan He; Quan Zhou; Yang Wen; Xiaohua Dai; Jianguo Wang (Mitochondrial DNA. Part B. Resources, 2019)
Platypus contaminatus attacked healthy hawthorn trees in China. The complete mitogenome of P. contaminatus was 15,712 bp in length. It contained 2 ribosomal RNA genes, 22 transfer RNA genes, 13 protein-coding genes and a 1038-bp long non-coding AT-rich region. This species showed rearrangements in mitochondrial genome. These changes included: (1) the reversal of the order of tRNATrp and tRNAGln genes; (2) tRNASer moved from its ancestral position (between cob and nad1) to the nad2–tRNAGln gene junction. Phylogenetic analysis using nucleotide sequences of 13 PCGs showed that P. contaminatus was closely related to Euplatypus parallelus, which was similar to the previous research.